2008
DOI: 10.1152/ajpcell.00381.2007
|View full text |Cite
|
Sign up to set email alerts
|

Fluid pressure modulates L-type Ca2+ channel via enhancement of Ca2+-induced Ca2+ release in rat ventricular myocytes

Abstract: This study examines whether fluid pressure (FP) modulates the L-type Ca(2+) channel in cardiomyocytes and investigates the underlying cellular mechanism(s) involved. A flow of pressurized (approximately 16 dyn/cm(2)) fluid, identical to that bathing the myocytes, was applied onto single rat ventricular myocytes using a microperfusion method. The Ca(2+) current (I(Ca)) and cytosolic Ca(2+) signals were measured using a whole cell patch-clamp and confocal imaging, respectively. It was found that the FP reversibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 49 publications
2
17
0
Order By: Relevance
“…Similar deformation-induced increases in Ca 2+ spark rate have been observed in the depth of atrial myocytes during sarcolemmal fluid-jet stimulation 39. Also, RyR2 mechanosensitivity could underlie the fluid-pressure induced increase in Ca 2+ -induced Ca 2+ releasability from the SR, observed in rat ventricular cardiomyocytes 40. Alternatively, there may be mitochondria-mediated responses,39 or currently unknown effects of fast-acting local signal transduction pathways that are relevant for RyR2 function and affected by the cytoskeleton 41…”
Section: Discussionsupporting
confidence: 58%
“…Similar deformation-induced increases in Ca 2+ spark rate have been observed in the depth of atrial myocytes during sarcolemmal fluid-jet stimulation 39. Also, RyR2 mechanosensitivity could underlie the fluid-pressure induced increase in Ca 2+ -induced Ca 2+ releasability from the SR, observed in rat ventricular cardiomyocytes 40. Alternatively, there may be mitochondria-mediated responses,39 or currently unknown effects of fast-acting local signal transduction pathways that are relevant for RyR2 function and affected by the cytoskeleton 41…”
Section: Discussionsupporting
confidence: 58%
“…Animal studies have shown that HIT in rats for 5 weeks results in 30 and 85% in the MCT1 and Na + /bicarbonate transporter, respectively, while MCT4 remained unchanged (Thomas et al, 2007). In humans, changes in the Na + /H + exchanger protein levels by 30% have been reported in the 4-week high-intensity sprint training study of Iaia et al (2008). Moreover, significant increases in MCT1 and Na + /H + exchanger protein densities have been found after HIT, especially when training bouts cause a significant accumulation of H + in the muscle (Mohr et al, 2007).…”
Section: High-intensity Training: a Powerful And Time-efficient Exercmentioning
confidence: 75%
“…Fluid flow was gravity driven (25-85 μl/min) to generate shear stresses from 0.34 to 1.15 dyne/cm 2 . The shear pressure was calculated for fluid flow in cylindrical tubes according to the equation as τ = 6μQ/π r 3 , where τ is shear stress or pressure (dyne/cm 2 ), μ represents the fluid viscosity, Q is the flow rate (ml/s), and r is the internal radius of the tube [21]. …”
Section: Methodsmentioning
confidence: 99%